STRATEGIES OF POLITENESS USED BY ENGLISH LECTURERS WHEN INTERACTING WITH THE STUDENTS IN LEARNING PROCESS AT UNIVERSITY LEVEL IN WEST SUMATERA - Yelfiza Yelfiza (International Conference on Languages and Arts, 2014)
This research studied types of strategies of politeness, which were used by the lecturers when they interacted with their students in learning process. Qualitative method with the techniques of recording was used to gather the data. Informants were the lecturers of English department who taught at odd semester 2013/2014 academic year. Sampling technique was purposive sampling. Instruments of the research were video and questionnaire. Data were analyzed through the some procedures, as providing the data and organizing them, exploring them by coding, using the code to gain a general description and deciding theme, presenting the findings, interpreting, and validating. Findings can be interpreted that the types of politeness used by the lecturers are categorized into two general kinds, positive and negative strategies. The positive strategies include making the students comforted, being consistent, being responsible, being industrious, being appreciative, and being aware. However, the negative strategies include being angry, being inconsistent, being irresponsible, being unaware, and being inappreciative. All kinds of positive strategies are suggested to be used when interacting with the students in learning process. Conversely, the negative strategies are suggested not to be used, with the exception, when the students break norms. Key words: strategies, politeness, interacting, learning, university